El cuerpo femenino, confinado y violentado: repensando la otra pandemia en casa desde una relectura de M. Merleau-Ponty y S. De Beauvoir - Avila Vera, Roger Park (Pontificia Universidad Católica del Perú, 2023)
The elaboration of this article stems from the interest in rethinking the conclusions of the study The other pandemic at home. In these we identified deficiencies in the prevention and immediate attention of the state system in the face of gender violence, which became even more evident during the SARS-CoV-2 pandemic in Peru. But, above all, we find a certain complicit silence that contributes to perpetuating cases of domestic violence against women in our country. To demonstrate this, we will start by explaining that the recognition of these deficiencies has an approach that stems from the exceptional circumstance of the pandemic and not from the structural problem of gender violence as such. Likewise, we will analyze confinement in terms of a new relationship of the human being with his around and the world in correspondence with the conceptual network of the body-world system of M. Merleau-Ponty. Finally, drawing on Simone de Beauvoir’s critique of the eternal feminine, we will interpret the forgetting of pre-confinement knowledge, coupled with the slightest suggestion that adequate preventive and corrective measures cannot be taken against gender-based violence, as an act of “bad faith”.

La elaboración del presente artículo parte del interés por repensar las conclusiones del estudio “La otra pandemia en casa”, en las cuales se reconocen falencias de la prevención y atención inmediata del sistema estatal frente a la violencia de género que, se hizo aún más evidente durante la pandemia del SARS-CoV-2 en el Perú. Desde nuestro punto de vista, existe un silencio cómplice que contribuye a la manutención de casos por violencia doméstica hacia la mujer en nuestro país. Para demostrar esto, empezaremos por explicar que el reconocimiento de las falencias tiene un abordaje que parte desde la circunstancia excepcional de la pandemia y no desde el problema estructural que representa la violencia de género como tal. Asimismo, analizaremos el confinamiento, en términos de una nueva relación del ser humano con su entorno y con el mundo en correspondencia con la red conceptual del sistema cuerpo-mundo de M. Merleau-Ponty. Finalmente, a partir de la crítica del eterno femenino de S. de Beauvoir, reinterpretaremos como un acto de “mala fe” el olvido hacia el conocimiento previo al confinamiento en conjunto con la más mínima sugerencia de que no se pueden tomar medidas preventivas y correctivas adecuadas contra la violencia de género.
The female body, confined and aggressed: Rethinking the other pandemic at home from a rereading of M. Merleau-Ponty and S. de Beauvoir
Keywords: Body; Pandemic; Violence; Confinement; Women; Cuerpo; Pandemia; Violencia; Confinamiento; Mujer; https://purl.org/pe-repo/ocde/ford#5.04.03